Online interaction in public speaking course: Implementation and challenges of MOOC in students exchange program - Hafifah, Gusti Nur (Universitas Islam Negeri Banda Aceh, 2024)
Three types of online interaction: Learner-Instructor; Learner-Learner; and Learner-Content, were facilitated profoundly during the public speaking class in the massive open online course using the SPADA-DIKTI learning management system. This paper explores in-depth how the online interactions occurred, the challenges, and the students' responses toward the program. The classroom setting was done fully online during one semester that consisted of 16 meetings and was participated by 40 university students throughout Indonesia. The learner-content is the most dominant interaction since the course was conducted fully online and learners completed several assignments based on the timeline. There were enough portions for learner-instructor interaction via the conference meeting class and social media group chat that allowed students to consult with the instructor directly. Although there were peer activities related to assignments and assessments, learner-learner interaction is the least happening since it can only be controlled during online synchronous meetings. Despite the students' enthusiasm for joining the course, the course objectives were not completely achieved. Only 50 % of the students passed the course and managed to complete the course learning activities. Some issues related to the workload of assignments, student motivation, and autonomous learning attitude in online courses have become problems.